Strategi PR untuk Meningkatkan Minat Pengungjung Taman Wisata @karangresik.id - Rohman, Indie Taufiqu; Anugrah, Dadan; Cholidah, Lida Imelda (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2022)
This study aims to find out how the strategy for managing the Instagram @karangresik.id account is. The research method used in this research is descriptive research where descriptive research is only a situation or event. The data techniques used by researchers in collecting research data were observation, interviews and document review. The results of the study show that the visual messages contained in Instagram @karangresik.id content aim to simplify and accelerate the audience’s understanding of the messages presented. Content created by Public Relations of Karangresik Tourism Park is equipped with distinctive colors in accordance with the company’s identity, so that it attracts the audience’s attention more to be able to visit Karangresik Tourism Park. Submission of information through video content is claimed to be more conveyable and fulfill the needs of visitors regarding the information sought while at the same time having an impact on Karangresik Tourism Park. Karangresik Tourism Park Public Relations considers that using Instagram stories optimally and creatively can make Karangresik Tourism Park attract more followers to join and create interactions related to products, services and business.